Reshaping the Ethics of Suicide Prevention: Responsibility, Inequality and Action on the Social Determinants of Suicide. (21st November 2017) - Fitzpatrick, Scott J
Abstract: Value judgements in research and political decision-making that exclude evidence for the social determinants of suicide suggest that evidence is not sufficient on its own to guide policy and practice, and that there is a lack of conceptual clarity with regard to decisions relating to the prioritization of problems, the allocation of resources, the translation of research into practice, as well as questions of responsibility for suicide prevention. In this work I seek to broaden conventional ethical debate about suicide through the use of public health ethics frameworks. I argue that despite espousing a public health approach, current suicide prevention strategies are based largely on individual-level theorizing. This emphasis on the individual works to responsibilize individuals and communities for suicide prevention and directs attention away from public policy and systemic inequities. Given continued high rates of suicide, especially among disadvantaged social groups and communities, comprehensive government action is required to address the social and political determinants of suicide. Normative justification for action in realizing these ends is critical. I conclude by proposing one practicable form of action to make values and value judgements in suicide prevention explicit so that alternative forms of ethical and political recognition and responsibility are acknowledged.